A novel limb‐salvage reconstruction strategy with a custom hemipelvic endoprosthesis and preserved femoral head following the resection of periacetabular tumors: A preliminary study. Issue 4 (29th June 2022) - Xie, Xianbiao; Jin, Qinglin; Zhao, Zhiqiang; Wang, Yongqian; Wang, Bo; Zou, Changye; Yin, Junqiang; Huang, Gang; Shen, Jingnan
Abstract: The treatment of periacetabular malignancy frequently challenges surgeons. To simplify the surgical procedure, we performed a novel reconstruction strategy preserving the femoral head for patients with periacetabular malignancies. We retrospectively reviewed 14 patients who underwent total en bloc resection of a periacetabular tumor and reconstruction of the hip joint with an individualized hemipelvic endoprosthesis and remaining femoral head from July 2015 to January 2019 at our center. Regions of pelvic resection: region II—4 (28.6%), region I + II—5 (35.7%), region II + III—2 (14.3%) and region I + II + III—3 (21.4%). The oncological outcomes were that 13 patients survived without disease and one patient survived with lung metastasis. None of the patients experienced local recurrence (range: 20–62 months; mean: 32 months). The incidence of postoperative complications was 35.7%, including delayed wound healing and deep venous thrombosis. No prosthesis‐related complications occurred until the last follow‐up in this study (range: 20–62 months; mean: 32 months). The mean Musculoskeletal Tumor Society functional outcome score was 23.2. The mean Toronto Extremity Salvage Score of the patients was 75.7 points, with a mean limb discrepancy of 1.51 cm (range: 0.5–3.2 cm). Reconstruction with preservation of the femoral head showed acceptable early functional and oncological outcomes, and it had an acceptable complication rate.